Perceived determinants of effective employee engagement in a South African bank - Holder, Kerry-Lee (My University, 2018)
Employee engagement is a relatively new concept which has come to prominence because of its link to individual performance and organisational success. About a decade ago the Gallup Organisation developed the Q12 survey to measure employee engagement and this caused a spike of interest in the topic, with research showing a decline in employee engagement. This highlights the importance of this research in identifying how employee engagement can be enhanced. Little is known about the factors that promote employee engagement in large bureaucratic organisations, like banks, and whether certain factors have a greater impact on employee engagement than others. Currently, in the bank in which the research was conducted, too much attention has been paid to the mechanical process of performance management rather than employee engagement and the willingness of employees to perform. This research aimed to identify the factors that promote employee engagement in a large bureaucratic organisation, namely a bank, and to discover which of these factors are perceived to have the greatest impact on employee engagement. Twelve in-depth structured interviews were held and a themed content analysis was conducted through which common themes and factors were derived. Ten factors were identified and ranked by the respondents as having the greatest impact on employee engagement. The results of this study highlight the factors that contribute the most to employee engagement. The top three factors found to have the greatest impact on employee engagement are: reward and recognition; coaching, social support, good leadership and an environment that nurtures trust and collaboration; and employees feel valued and are treated fairly with respect and dignity. The results of this study provide guidance to organisations by way of a list of factors that managers can use to improve employee engagement. All the factors should be considered, but special attention should be paid to the top three factors identified in this study.
MBA Thesis
Keywords: Employee motivation -- South Africa. Banks and banking -- South Africa.